O cotidiano do trabalho de enfermagem na clínica cirúrgica de um hospital público em São Luís-Maranhão - Sousa, Santana de Maria Alves de (2009)
The routine is the daily life of every human. It is a part of the routine life our work, private life, leisure activities and resting period. The daily routine is the period when our dayby- day activities happen and when we establish our relations, allowing the changing possibilities and the chance to build something new. This study is aimed at the daily routine of the nursing activity, having as a goal the understanding of the nurses routine at the surgical clinic of a public hospital in São Luis MA, and analyze this routine, starting form the hospital practices. The research was carried out through participative observation, interviews and the analysis of secondary data sources which regulate the nursing work. The data gathering started in July 2006 and ended in September 2007. The data resulting from the interviews and observation have indicated two categories: the nursing work routine and the reflections regarding the routine; and connected to the first category the work process and condition. The nursing care routine is characterized by the predominance of female workers, and the social and technical division of the activities among their members, nurses, technical, and nursing assistants, each one with their respective routines, prevailing the hospital practices, the precarious job contracts, with double, triple shifts are common in the surgical clinical nursing routine. The second category reveals the routine conceptions of the studied individuals. Their routine, according to their opinion, although repetitive is not equal, since they are dealing with different people with different clinical conditions. The importance of this study is to encourage in the researched individuals the urge for new ways of learning, for the logic of discovery, even with all the monotony and the apparently boredom of the work routine